Lima pilar hukum islam: memahami esensi dan relevansi al-qawa’id al-fiqhiyyah al-kubra - Artika, Ririn D (Maliki Interdisciplinary Journal, 2025)
The complexity of contemporary legal issues, such as the digital economy, bioethics, and the environment, demands a systematic methodological framework in addressing fiqh issues, so this article comprehensively examines the philosophical essence and practical relevance of the Five Basic Principles of Fiqh (Al-Qawa’id Al-Fiqhiyyah Al-Kubra) as a universal foundation (kulli) and the main pillar in the Islamic legal system. These five fundamental principles include Al-Umuru bi Maqashidiha (Every matter depends on the intention), Al-Yaqinu La Yuzalu Bisy-Syak (Conviction cannot be removed by doubt, guaranteeing legal certainty), Al-Masyaqqah Tajlibu At-Taysir (Difficulty brings ease, the basis of rukhshah), Adh-Dhararu Yuzal (Harm must be eliminated, underpinning the protection of life and the environment), and Al-’Adatu Muhakkamah (Customs can be the basis of law, providing flexibility) not just theoretical tools. On the contrary, a deep understanding of these rules is the key to facilitating the determination of law (istinbath) on new cases, ensuring that fiqh can be presented as a more orderly, systematic, and adaptive science, so that it is relevant as a progressive solution to the challenges of the community in the modern era and globalization.